Challenges in scaling agile software development in offshoring environment - Bhattarai, Suresh Kumar (My University, 2011)
Corporate decision to scale Agile Software development methodologies in offshoring environment has been obstructed due to possible challenges in scaling agile as agile methodologies are regarded to be suitable for small project and co-located team only. Although model such as Agile Scaling Model (ASM) has been developed for scaling Agile with different factors, inabilities of companies to figure out challenges and addressing them lead to failure of project rather than gaining the benefits of using agile methodologies. This failure can be avoided, when scaling agile in IT offshoring environment, by determining key challenges associated in scaling agile in IT offshoring environment and then preparing strategies for addressing those key challenges. These key challenges in scaling agile with IT offshoring environment can be determined by studying issues related with Offshoring and Agile individually and also considering the positive impact of agile methodology in offshoring environment. Then, possible strategies to tackle these key challenges are developed according to the nature of individual challenges and utilizing the benefits of different agile methodologies to address individual situation. Thus, in this thesis, we proposed strategy of using hybrid agile method, which is increasing trend due to adaptive nature of Agile. Determination of the key challenges and possible strategies for tackling those challenges are supported with the survey conducted in the researched organization.